Securing Digital Wallet Loyalty: Unveiling the Impact of Privacy and Security - Utomo, Rio Guntur; Yasirandi, Rahmat (Universitas Negeri Semarang, 2024)
Purpose: The study investigates the fast-evolving fintech landscape, specifically the impact of digital wallets on the financial industry. It focuses on the competitive digital wallet market in Indonesia, examining how service quality influences user satisfaction and loyalty in a saturated market. By integrating a Security variable into the E-Servqual method, this research aims to offer a new perspective on assessing the effects of digital wallet services on user satisfaction and loyalty. Methods: This study employs the Modified E-Servqual model with an added Security variable to explore how service quality variables like Site Organization, Efficiency, Personal Needs, Privacy, Reliability, Responsiveness, Security, and User’s Friendliness impact customer satisfaction and loyalty in digital transactions. Surveying 287 digital wallet users, mostly GoPay, OVO, ShopeePay and DANA, the research provides a detailed analysis of these variables' effects on E-Customer Satisfaction and E-Customer Loyalty. Result: The findings show that digital wallet users value certain service quality aspects differently in terms of their impact on satisfaction and loyalty. While variables like Reliability, User’s Friendliness, Personal Needs, Privacy, Security, and Efficiency significantly influence user satisfaction, Site Organization and Responsiveness do not. This highlights the importance of security and efficiency in enhancing user satisfaction and loyalty in digital wallets. Novelty: The study's novel contribution is integrating a Security variable into the E-Servqual method, enhancing the assessment of digital wallets' inherent security risks. This integration provides a detailed analysis of how security impacts user satisfaction and loyalty, alongside other service quality factors. This systematic evaluation offers new insights for improving service quality, benefiting companies in the competitive digital wallet market, and informing future research on customer loyalty and provider success.